Women, War & Peace: War Redefined - Disney, Abigail; Higan, Pamela; Reticker, Gini (PBS, 2011)
“War Redefined” challenges the conventional wisdom that war and peace are men’s domain through incisive interviews with leading thinkers, Secretaries of State and seasoned survivors of war and peace-making. Interviewees include Secretary of State Hillary Clinton; Liberian peace activist Leymah Gbowee; Bosnian war crimes investigator Fadila Memisevic; and globalization expert Moisés Naím. Narrated by: Geena Davis.